Metre and memory - Byrne, S (British Academy, 2019)
This chapter looks at Tony Harrison's self-appointed role as Bard and considers the significance of this in relation to Ancient and Classical Greek ideas about poetry and poets, particularly the public function of poetry and the relationship between poetry and memory.